The Instrumentalization of Metaphors in the Management Field: Reflections from the use of the Book “The Art of War” on Business - Luiz Gustavo Lara; Fabio Vizeu; Elizeu Barroso Alves (BBR: Brazilian Business Review)
The debate about the use of metaphors in the organizational context in the last decades has not been exhausted, especially in discourse studies. Inserting itself in this discussion, the present essay problematizes the anachronistic dimension in the use of metaphors in the field of management. From a hermeneutic-critical perspective, we argue that the use of metaphors in managerial literature sometimes reflects a utilitarian and anachronistic distortion of the contexts originating in metaphorical symbolic forms. In this sense, the strategic use of language can inhibit the interpretive autonomy of individuals, that is, colonize their interpretive horizons by the persuasive induction of simplistic and utilitarian worldviews about organizational reality. We use the essay form as a method, and we rely theoretically on Alvesson’s critical approach, on the hermeneutics by Gadamer and Ricoeur, and on Habermas’ Critical Theory. We illustrate our argument by recurring use of the work “The Art of War” as a metaphor for managerial practice.